Utilisation du quadrangle « discrete shear » pour la génération des surfaces d’influence des efforts de plaque: Exemples de mise en oeuvre avec Code_Aster - Lévêque, Philippe; Bacchus, Florent (European Journal of Computational Mechanics, 2008)
Concept of influence surface is the appropriate tool to determine the extreme structural response values of structures under the effect of moving loads. The action of road traffic moving on bridge deck is computed this way. Influence surface generation method is based on Maxwell-Betti’s theorem of reciprocity. This paper presents the use of the « discrete shear » formulation of a thick plate quadrangle finite element to generate the influence surfaces of internal forces in a slab bridge using the Code_Aster free software.